The Contribution of Cattle Farming Business towards Income Farmer Families at New Reyan Farmer Group West Lombok - Fakhihatul M, Siti; M.Yasin, M.Yasin; Santi Rengganis, Baiq (International Journal of Sharia Business Management, 2023)
Beef cattle farming business can be said to be successful if it has contributed income and can meet the daily needs of farmers. This study aims to determine the net income of farmers from horticultural crop farming, net income of farmers from cattle farming, net income of farmers from other businesses, net income of farmers families, the contribution of cattle farming to the income of farmers household, and to determine the correlation between cattle farming business with the income of farmers household. This research was conducted in Reyan Baru livestock farmers group located in South Gerung Village, Gerung District. The study started from March to April 2023 using the survey method. Determination of the location of this study was done intentionally (Purposive). The number of respondents taken as many as 25 responden with criteria of group members who have two activities, namely cattle breeding and farming. The results showed that the net income of farmers from farming horticultural crops during the growing season (six month) an average of Rp39.368.896, farmers 'income from cattle farming business suffered an average loss of Rp-8.184.000, net income of farmers from other businesses an average of Rp2.664.000, total net income of farmers families an average of Rp33.961.896, the contribution of cattle farming to the income of farmers household amounted to -23,76%. Cattle farming business economically has not contributed to the income of farmers house hold. Due to because at the time of the study conducted cattle prices are experiencing a significant decline after the PMK attack. From the analysis obtained correlation coefficient (r) se 0.10641. It mean that the cattle farming business has a very weak relationship with the income of the farmer's family